Social protection: potential for improving HIV outcomes among adolescents - Meinck, F; Cluver, L; Orkin, F; Hodes, R; Sherr, L; Lim ah Ken, P; Winder-Rossi, N; Wolfe, J; Vicari, M (BioMed Central, 2015)
Introduction Advances in biomedical technologies provide potential for adolescent HIV prevention and HIV‐positive survival. The UNAIDS 90–90–90 treatment targets provide a new roadmap for ending the HIV epidemic, principally through antiretroviral treatment, HIV testing and viral suppression among people with HIV. However, while imperative, HIV treatment and testing will not be sufficient to address the epidemic among adolescents in Southern and Eastern Africa. In particular, use of condoms and adherence to antiretroviral therapy (ART) remain haphazard, with evidence that social and structural deprivation is negatively impacting adolescents’ capacity to protect themselves and others. This paper examines the evidence for and potential of interventions addressing these structural deprivations. Discussion New evidence is emerging around social protection interventions, including cash transfers, parenting support and educational support (“cash, care and classroom”). These interventions have the potential to reduce the social and economic drivers of HIV risk, improve utilization of prevention technologies and improve adherence to ART for adolescent populations in the hyper‐endemic settings of Southern and Eastern Africa. Studies show that the integration of social and economic interventions has high acceptability and reach and that it holds powerful potential for improved HIV, health and development outcomes. Conclusions Social protection is a largely untapped means of reducing HIV‐risk behaviours and increasing uptake of and adherence to biomedical prevention and treatment technologies. There is now sufficient evidence to include social protection programming as a key strategy not only to mitigate the negative impacts of the HIV epidemic among families, but also to contribute to HIV prevention among adolescents and potentially to remove social and economic barriers to accessing treatment. We urge a further research and programming agenda: to actively combine programmes that increase availability of biomedical solutions with social protection policies that can boost their utilization.